Investigation of spectral nulls using convex geometry in OFDM systems - Kyaw, Nyi Nyi Ko. (2008)
Orthogonal Frequency Division Multiplexing (OFDM) offers spectral efficiency and low power consumption to the communication system. the major impairment encountered in OFDM system is the multipath fading in the communication channel; which leads to loss of data. OFDM also offers immunity form the multipath fading nature of communication channels.